Literature Review: Threat of Artificial Intelligence (Ai) Cyber Attacks on Data Security - Apriansyah, Ferryma Arba; Ujianto, Erik Iman Heri; Rianto, Rianto (International Journal of Education, Information Technology, and Others, 2024)
The purpose of this study is to present an overview of the approaches and areas of concentration in data security identification. The report analyzes AI cyberattacks on Indonesian data security through a review of the literature. In order to find relevant papers, search terms like "Cyber Attacks," "Artificial Intelligence," and "Data Security" were used in this study. 80 of the 1,057 studies that were found between 2019 and 2023 were employed in this analysis. The outcomes of this evaluation of the literature can help future researchers conduct more in-depth studies on data security. A number of factors, such as extending the study's purview, incorporating a wider range of topics, and including people who may provide additional insights, might be taken into account for future data security research.